Hip Hype: FAI Syndrome, Amara's Law, and the Hype Cycle - Kassarjian, Ara (Seminars in Musculoskeletal Radiology, 2019)
Femoroacetabular impingement (FAI) has taken us on a roller-coaster ride of innovation, heightened expectations, disillusionment, and confusing diagnostic and treatment pathways. This article reviews and analyzes the phases of FAI diagnosis and treatment over the past 15 years and discusses its parallels to Amara's law and Gartner's hype cycle.
Keywords: hip; impingement; MRI; femoroacetabular; joint